2020
DOI: 10.23960/jiia.v8i3.4470
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pendapatan Usahatani Dan Biaya Pokok Produksi Padi Rawa Lebak Di Desa Serijabo Kecamatan Sungai Pinang Kabupaten Ogan Ilir

Abstract: This research aims at determining the farm income and main production cost of rice on lowland swamp in Serijabo Village Sungai Pinang Sub-District. This field research was conducted in February-March 2019. The location was one of central productions in Sungai Pinang Sub-District. The sample size was 51 rice farmers who were selected using simple random sampling method. The data were analyzed by using farm income and main production cost analysis with 95 percent of confidence level. The study showed that the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
2
0
2
Order By: Relevance
“…The interviews revealed that farming activities as the livelihood is not entirely reliable as their main source of income. This is in line with study by [10], which revealed that the income of farmers who only grow rice is smaller than other systems that cultivate more than one crop commodities, thus farmers still have to look for other livelihoods besides farming to meet household needs. Based on the calculation results, one phenomenon was encounterd, namely that the income of farmers nowadays is greater than the income when farmers were still cultivating their farmland.…”
Section: Economic Impactsupporting
confidence: 82%
“…The interviews revealed that farming activities as the livelihood is not entirely reliable as their main source of income. This is in line with study by [10], which revealed that the income of farmers who only grow rice is smaller than other systems that cultivate more than one crop commodities, thus farmers still have to look for other livelihoods besides farming to meet household needs. Based on the calculation results, one phenomenon was encounterd, namely that the income of farmers nowadays is greater than the income when farmers were still cultivating their farmland.…”
Section: Economic Impactsupporting
confidence: 82%
“…1.20. The ratio of revenues to total costs that is greater than 1.00 indicates that it is economically profitable and feasible to operate [13]. Rice production in the Lebak swamp can be increased by applying site-specific technology and increasing the frequency of extension.…”
Section: Analysis Of Rice Farmers' Income After Optimizing the Use Of...mentioning
confidence: 99%
“…Luas total lahan rawa lebak di Kabupaten Ogan Ilir adalah 61.940ha, dengan lahan yang sudah dikembangkan seluas 33.986ha dan lahan yang belum dikembangkan seluas 27.954ha (Kasih et al, 2020). Artinya jika kita melihat luas lahan rawa lebak yang belum dimanfaatkan, ini merupakan potensi yang bisa dikembangan menjadi areal lahan pangan untuk menyokong produksi pangan secara nasional khususnya jagung dan kedelai, apalagi jika diiringi dengan metode yang tepat.…”
Section: Pendahuluanunclassified